Christin Sharashidze - A Woman From The Past Dedicated To The Future - Tcholadze, Lolita (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
One of the most important achievements of the First Republic of Georgia was giving women the right to vote in elections. Georgian Constituent Assembly consisted of 5 women: Elizabeth Bolkvadze, Minadora Toroshelidze, Christin Sharashidze, Eleonora Ter-Farsegova-Makhviladze, and Ana Solorashvili. The subject matter of the article is the public work of Christin Sharashidze (1887-1973)who was one of the distinguished women, a teacher, journalist, scientist, big fan of Georgian national culture. Christin Sharashidze was a member of several charity-scientific communities. In 1917 she was elected as a board member of the organization “ spreading reading and writing knowledge among Georgians”, she was a founding partner of “Georgian university founding community”. She graduated from this university in 1931 with a specialization in teaching. C. Sarashidze was a dedicated servant of the library work for many years. Initially, she managed the library branch of the historical-ethnographic museum. In 1929 when the funds of the historical-ethnographic museum united with the museum of Georgia, she became a staff member of the museum. In 1934 she started working at the university, in 1935 she worked in a former “Metekhi” library. Later she became a famous scientist, unbelievable expert of Georgian manuscripts and the author of the fundamental work-related to South Georgia. She prepared important works regarding the Georgian printed history, including “The first print house in Georgia (1709-1722) - the history of Georgian printed word” (1955). His private archive: biographical materials, creative correspondence, photos and different materials, overall 2938 archival works kept in the national center of manuscripts.